Creating firm value, overcoming organizational inertia through the marketing value chain - Palomino-Tamayo, Walter (2022)
Purpose: Technology may produce disruptive changes and market turbulence in any industry. Organizational inertia becomes relevant as a factor that adversely affects organizational transformation; this study aims to examine how to overcome it and its consequences to firms. Design/methodology/approach: The model estimation with seemingly unrelated regression and two-stage least square. The authors build a data set of years 2015–2019 from the Lima Stock Exchange firms to test the hypotheses. Findings: In this research, using the evolutionary-ecological theory of Hannan and Freeman, the study shows the consequences of organizational inertia on marketing intensity and subsequently on firms' financial results. Originality/value: This study presents an inter-functional model that links organizational behavior, marketing and finance functions, through the marketing value chain to overcome organizational inertia and create firm value.